Key differences between severity of disciplinary issues and medical student insights. Issue 8 (28th May 2019) - Burgess, Raquel; Vanstone, Meredith; Mountjoy, Margo; Grierson, Lawrence
Abstract : Context: This study explores the reliability of tools designed to rate the type of remediable medical student offences, their severity, and the quality of student insight in response to the remediation, and tests the relationships between these three constructs. Methods: Data were collected via retrospective appraisal of remediation files from the 2009–2016 incoming classes of McMaster University's medical programme. Across two studies, 12 faculty members categorised the offences by type (academic or professionalism), and rated severity and insight by way of single anchored Likert scales. In Study 1, Krippendorff's alpha and independent, two‐way, consistency type, average measures ( k = 6), random‐effects inter‐rater reliability analyses were conducted to assess the inter‐rater reliability of ratings of the measures. In Study 2, independent samples t ‐tests were conducted for the severity and insight measures as a function of offence type. Pearson correlations were used to assess the relationship between severity and insight as a function of offence type. Results: High inter‐rater reliability was found with respect to the type of offence (α = 0.86), severity (0.92) and student insight (0.88). Mean (±standard deviation) ratings of severity are significantly higher for professionalism (4.37 ± 1.20) than academic offences (2.89 ± 1.25), t (73) = −5.3, p < 0.001, | d | = 1.21, whereas the opposite is true for ratings of insight, (professionalism, 3.19 ± 1.37; academic, 4.48 ± 1.01), t (73) = 4.6, p < 0.001, | d | = 1.07. Ratings of severity and insight are moderately negatively correlated for both academic ( r = −0.64, p < 0.001, n = 38) and professionalism offences ( r = −0.57, p < 0.001, n = 37). Conclusions: Professionalism offences are perceived as more severe and are associated with lower insight than academic offences, pointing to the difficulty that learners face in assessing the constitution of a professionalism offence. This illustrates a need for deeper consideration about remedial strategies for lapses in professionalism. Abstract : Burgess et al. demonstrate that students who commit professionalism offences are perceived as demonstrating lower quality of insight in response to remediation relative to those who commit academic offences.